Maize (Zea mays) genotypes for intercropping with cassava (Manihot esculenta) in Southern Nigeria 1. yield responses - Ezumah, H.C. (1990)
In order to ascertain the recommended changes as breeders release new improved maize varieties for use in cassava based systems in tropical Alfisol in southern Nigeria, the effects of maize variety and population on cassava root and maize grain yield, under the intercropping system, were evaluated. Five maiZe varieties, of contrasting growth habits, each at five populations (10, 20, 40, 80 and 160 x loa plants/ha) were intercropped with cassava. The results of a two-year study showed that a maize population of 40-80 x loa plants/ha gave no significant reduction in yield of intercropped cassava. Population response varied with maize growth habit, the short early maturing types requiring higher maize populations. Majze grain yield tended to decline or remained constant at the highest population (160,000 plants/ha). These results indicate that maize varieties selected by breeders for high yields as monocrops behave similarly wlien intercropped with cassava i.e., yield responses of soiecropped maize can be used to predict accurately responses when it is intercropped with cassava. However, their effects on associated cassava yield vary with maize growth habits, especially at maize populations higher than 40,000 plants/ha